FECAL MICROBIOME DISTINGUISHES ALCOHOL CONSUMPTION FROM ALCOHOLIC HEPATITIS BUT DOES NOT DISCRIMINATE DISEASE SEVERITY - Smirnova, Ekaterina (Hepatology, 2020)
BACKGROUND AND AIMS: The role of the intestinal microbiome in alcoholic hepatitis is not established. The aims of this study were to: (1) characterize the fecal microbial ecology associated with alcoholic hepatitis, (2) relate microbiome changes to disease severity and (3) infer the functional relevance of shifts in microbial ecology. METHODS: The fecal microbiome in patients with moderate or severe alcoholic hepatitis (MAH and SAH) was compared to healthy (HC) and heavy drinking controls (HDC). Microbial taxa were identified by 16S pyrosequencing. Functional metagenomics was performed using PICRUSt. Fecal short chain fatty acids (SCFA) were measured using an LC/MS platform. RESULTS: 78 participants (HC, n=24; HDC, n=20; MAH, n=10; SAH, n=24) were studied. Heavy drinking had a distinct signature compared to healthy controls with depletion of Bacteroidetes (46% vs 26%; p=0.01). Alcoholic hepatitis was associated with a distinct microbiome signature compared to heavy drinking controls (AUC=0.826); differential abundance of Ruminococcaceae, Veillonellaceae, Lachnospiraceae, Porphyromonadaceae, and Rikenellaceae families were the key contributors to these differences. The beta diversity was significantly different amongst the groups (PERMANOVA p < 0.001). Severe alcoholic hepatitis was associated with increased Proteobacteria (SAH 14% vs. HDC 7% and SAH vs. HC 2%, p=0.20 and 0.01 respectively). Firmicutes abundance declined from HDC to MAH to SAH (63% vs. 53% vs. 48% respectively, p=0.09 HDC vs. SAH). Microbial taxa did not distinguish between moderate and severe alcoholic hepatitis (PERMANOVA p= 0.785). SCFA producing bacteria (Lachnospiraceae and Ruminococcaceae) were decreased in alcoholic hepatitis, and a similar decrease was observed in fecal short chain fatty acids among alcoholic hepatitis patients. CONCLUSIONS: There are distinct changes in fecal microbiome associated with development of but not severity of alcoholic hepatitis.